Involuntary Career Changes: A Lonesome Social Experience - Masdonati, Jonas; Frésard, Caroline É.; Parmentier, Michaël (Frontiers in Psychology, 2022)
Like any other career process, career changes are influenced by relationships. Moreover, involuntary career changes are a challenging, yet understudied, career transition. Based on a relational perspective of work and careers, we investigated the way people’s social environment affects the process and experience of involuntary career changes. Specifically, we aimed to identify the sources of relational influences and to understand how these influences affect career changes. Semi-structured interviews were carried out with 14 adults who were forced to change career because of unemployment or health issues. Through thematic analysis, we identified three sources of relational influences (personal, work, and institutional environment) and three forms of influence that others had on career changes (positive, negative, and ambivalent). These influences manifested at four distinct moments of the process: When participants were leaving their former job, when they were shifting between their former occupation and a new livelihood, when they were exploring new career options, or when they were trying to implement their new career plan. Overall, results suggest that involuntary career changes are deeply shaped by heterogeneous and differentiated relational influences. The effect of the personal environment varied depending on the moment of the career change process. In particular, family and friends tended to be perceived as barriers when it came to shifting from the old to a new occupation and implementing a new career plan. The work environment mostly had a negative effect on the career change experience, suggesting the labor market might be somewhat refractory toward adult career changers. Institutions played a critical role throughout the change process, with support structures often being perceived as inappropriate, but with guidance professionals generally recognizing participants’ difficulties. Moreover, diverse forms of ambivalence characterized the identified relational influences, which were sometimes both appreciated and avoided or had ambiguous and fluctuating effects. Finally, although being a fundamentally social experience, involuntary career changes were also characterized by moments of loneliness that reflected the inadequacy of available support and a sense of shame associated with the status of career changer. Study limitations, research perspectives, and practical implications at the labor market, institutional, and individual levels are addressed.